Pengaruh Program Modifikasi Perilaku Berbasis Behavioral Chaining terhadap Motivasi Belajar Mahasiswa: Studi Kuasi-Eksperimen - Dina Mariana Siregar; Eva Amalputra; Yabes Sumual; Cindy Damayanti; Reva Mokodompit (Jurnal Sostekmas: Jurnal Sosial, Teknologi, dan Pengabdian Masyarakat, 2026)
Low learning motivation is one of the main predictors of academic procrastination and declining achievement among university students. This study aimed to examine the effect of a behavior modification program based on behavioral chaining principles on students’ learning motivation. A quasi-experimental nonequivalent control group design (pretest–posttest) was employed, involving 60 students assigned to an experimental group (n = 30) and a control group (n = 30) through purposive sampling based on low-to-moderate learning motivation scores. The experimental group received a six-session behavioral chaining program that broke down effective study behavior into a sequence of mutually reinforcing behavioral links. Learning motivation was measured using the Learning Motivation Scale (30 items, α = .912). A paired-samples t-test revealed a significant increase in the experimental group (t(29) = 11.08, p < .001), whereas the control group showed no significant change (t(29) = 1.51, p = .143). An independent-samples t-test on gain scores indicated a significant difference between the two groups (t(58) = 7.19, p < .001) with a very large effect size (Cohen’s d = 1.86). These findings suggest that a behavioral chaining–based behavior modification program is effective in enhancing students’ learning motivation and may be considered a practical intervention within higher-education guidance and counseling services.